ТАРЖИМА ВА ТАЛҚИН (Махтумқули шеърлари таржималари мисолида) - Сапаева, Ф. (SCIENCE and SOCIETY, 2019)
The article is devoted to the study of translation of poems of Makhtumkuli into the Uzbek language. On the example of translation of the poems of Makhtumkuli into Uzbek the author analyzes the translators’ skill in using words and suggests discussing the value of a word in the literary-artistic translation.